The Impact of E-Banking on Performance of Financial Institutions in Uganda: A Case Study of DFCU Bank Kabale Branch. - Amutuheire, Grant (Kabale University, 2024)
The purpose of the study was to find out the impact of e-banking on the performance of financial institutions in Uganda: A Case of DFCU Bank, Kabale Branch. The study was guided by specific objectives, namely, to find out the forms of E-banking used in DFCU Bank, determine the relationship between E-banking and the performance of DFCU Bank, and examine the impact of E-banking on the performance of DFCU Bank in Kabale District. This study employed a descriptive research and survey design, as well as quantitative and qualitative approaches, Using simple random and purposive sampling techniques, a total of 67 respondents were selected for this study. In addition, questionnaires and interviewing methods of data collection were used. The research findings showed that the forms of e-banking used in the DFCU bank in Kabale district were mobile banking, as represented by 33%, internet banking, as represented by 30%, electronic cards, as represented by 22%, and electronic fund transfers, as represented by 15%. The study discovered a strong significant relationship (r =.761; sig .. 05) between electronic banking and financial institution performance, particularly DFCU Bank in the Kabale district. According to the study findings, 33% of the majority. of respondents indicated that electronic banking had a positive impact on the performance of financial institutions in the Kabale district, particularly DFCU Bank. According to the study, financial institutions that have not yet implemented some e-banking tools should do so in order to improve their performance and serve their customers as expected.